Effects of justicia wynaadensis extracts on spore germination of pathogenic and storage fungi - SULLIMADA UTHAIAH PONNAMMA,; KIRGANDUR MANJUNATH, (International Journal of Pharma and Bio Sciences, 2017)
The potential risk to health with the use of chemical fungicides in/on foods has necessitated the search for natural alternatives, such as those from plants. The present investigation evaluates the in vitro antifungal effects of the aqueous and methanolic extracts of Justicia wynaadensis (Nees) T. Anders at concentrations of 1mg/ml, 5mg/ml and 10mg/ml against certain pathogenic- and storage-fungi, by assaying for the germination of spores by the slide germination test. It was observed that the most susceptible organism to the aqueous extract at the minimum concentration tested (1mg/ml) was R. stolonifer (97% inhibition), followed by P. chrysogenum (42.9% inhibition) and F. fusariodes (26.7% inhibition), whilst the conidia/spores of all the fungal species tested were susceptible to 1mg/ml of the methanolic extract compared to the control. Thus, there is significant potential for the extract of J. wynaadensis to be used for crop protection and as a food preservative, especially as a ‘non-toxic preservative’.